INOVASI SERVICE BLUEPRINT PADA ERA PANDEMI COVID-19: STUDI KASUS DESA WISATA CARANGSARI - I Ketut Muliadiasa; Ida Bagus Made Wiyasha (JURNAL KEPARIWISATAAN, 2023)
Consistency of service quality was a strategic factor in achieving sustainable tourism. This study aimed to design a service blueprint for tourist products in the Carangsari village. There were 4 (four) service blueprints intended as prototypes for the tugek mask dance, trekking, kecak dance, and accommodation services. The service blueprint was a flow chart of activities from the four tourist products the Carangsari tourist village offered. In the service blueprint protype there were 2 (two) factors studied: the sequence of tourist activities and the function of the service providers involved in the Carangsari tourist village. For the order of tourist activities, the design of a service blueprint was adjusted for each tourist product offered. The service provider function included 5 (five) functions applicable to all tourism products: physical evidence, customer actions, public service actions, back staff actions, and support and system actions. The head of the Carangsari tourism village, representing the tourism stakeholders of the Carangsari tourism village, expressed his appreciation for the design of the prototype of the service blueprint to provide consistency in the quality of service for tourists. The prototype of the service blueprint should be updated by the dynamics of the tourism industry. Due to time limitations, impacts and results of service blueprint prototype applications for four tourism products offered by Carangsari Tourism Village have not been evaluated. Conducting another research program to evaluate the effectiveness of service blueprint prototype applications is strongly suggested.